Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams CONTENTS PAGE PREFACE 7 Chapter I. BRITAIN'S SOCIAL PROGRESS REVIEWED. 9 Chapter II. THE PRIMARY NEEDS AND RISKS 20 Chapter III. SOCIAL SECURITY IN ACTION 28 Chapter IV. THE STORY OF ADAM BLACK AND EVE BROWN 37 Chapter V. ADMINISTRATION AND FINANCE 50 POSTSCRIPT 59 LIST OF CHARTS PAGE POVERTY SHORTENS LIFE OVERCROWDING AND INFANT MORTALITY 10-11 UNEMPLOYMENT 15 POVERTY AND ITS SOURCES 15-19 THE CHANCES OF SURVIVAL IMPROVED 22-23 REQUIREMENTS 26-27 THE PROBLEM OF RENT 39 SOCIAL SERVICES DEVELOPED 32-33 THE SIX CLASSES AND THE AGE GROUPS 38-39 HOW THE AGE GROUPS SHIFT 43 ADMINISTRATION COMPARED 48-49 FINANCE 52-53 THE BURDEN ON THE EMPLOYER 56 THE BURDEN ON THE EXCHEQUER 57 15X/2/566/303